Enhancing Learning Outcomes and Learning Motivation through Quizizz-Based Gamification in Elementary School IPAS Learning - Raudha Hadi; Furqan Ishak Aksa; Rima Meilita Sari (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aimed to examine the effect of Quizizz-based gamification on students’ learning outcomes and learning motivation in Integrated Science and Social Studies (IPAS) learning at the elementary school level. A quantitative quasi-experimental design employing a non-equivalent control group pretest–posttest design was used. The participants consisted of 34 third-grade students from State Elementary School 3 Langsa, Indonesia, divided equally into experimental and control groups. Data were collected using a learning outcomes test and a learning motivation questionnaire. Statistical analyses included descriptive statistics, normality tests, homogeneity tests, Independent Samples t-tests, and effect size analysis. The findings revealed that the experimental group achieved a higher posttest mean score (85.44) than the control group (77.06), with a significant difference between groups (t = 4.826, p < 0.001). Learning motivation was also significantly higher among students receiving Quizizz-based gamification (t = 4.118, p < 0.001). Large effect sizes were obtained for learning outcomes (d = 1.71) and learning motivation (d = 1.41). The findings support the integration of gamified digital platforms to enhance elementary students’ academic achievement and motivation.